Erdhütten der Eskimo im Dorf in Okak im Winter : [ca. 1900] - Hettasch, Paul, 1873-1949. (2001)
Black and white photograph of Inuit children outside an Inuit family house in Okak, circa 1900. Black and white photograph of Inuit children outside an Inuit family house in Okak, circa 1900.